Storying Emotional Geographies among dispossessed Ibaloi and Kankanaey miners - Ocampo, Lou Angeli (Philippine Social Sciences Review; PSSR Vol. 73 No. 2 2021, Ed. Jorge V. Tigno, 2024)
The practices of local communities are shaped by stories of relation with the environment and resource access. The paper looks at emotions to provide an alternative perspective on the experiences of land and resource marginalization among the Ibaloi and Kankanaey small-scale gold miners in Itogon, Benguet. Emotions are not often given emphasis in studies although these are powerful indicators of how bodies subjected to precarious work bring about sentiments of fear, uncertainty, anger and conflicted emotions of guilt. This paper aims to contribute to the investigation of emotional geographies to illuminate economic relations that perpetuate dispossession and inequalities. It reframes the current involvement of indigenous miners in subcontract mining as a story of survivance amidst various forms of dispossession that threaten the reproduction of indigenous relation with the land and the indigenous mining system. Dispossession takes place along with environmental degradation as lands that hold cultural significance are transformed or destroyed by corporate mining activities.